Potential of patient portals to enhance adolescent asthma care engagement - Emma J. Clark, MSc; Whitney Chan; Emily Gao; Ilana Radparvar; Rong Guo, MS; Ana Gomez, BA; Nashica Hamm, BS; Dariush Kafashzadeh, MD; Gery W. Ryan, PhD; Mindy K. Ross, MD, MAS, MBA (Health Care Transitions)
Importance: Electronic health record-based patient portals hold promise for health care transition (HCT), particularly for chronic conditions like asthma. Objective: To understand the potential of a portal-based asthma care management module in adolescent patients with asthma and evaluate its performance and usability. Methods: We completed semi-structured interviews to determine adolescent perceptions of a portal-based asthma care module and its potential for HCT. We prototype tested a portal-based asthma management module with adolescent patients (12–17 years old) with asthma for their upcoming pediatric pulmonary clinic visits and measured its performance and usability. We reported descriptive statistics for survey data, and content analysis for interviews. Results: Sixteen adolescents completed interviews. Most interviewees favored the idea of using a module before visits and believed it could help them with HCT. We identified five themes: adolescent familiarity with the patient portal, perceived benefits, perceived barriers, suggestions for usability, and perspectives on a portal module’s potential role in supporting their asthma and HCT readiness for asthma management. Eleven adolescents tested the module. The percentage of asthma data captured from the physician visit notes with the module was higher compared to notes without (93.1 % [95 % CI: 90.3, 95.3] vs. 74.6 % [95 % CI: 71.0,77.6], p < 0.005). The average System Usability Scale score of the module was 71 ± 9.6 (considered above average). Conclusions: Our findings support the potential of portal-based based management modules to be accepted by adolescents with asthma and to engage adolescents more in their own care. We will continue to iterate the module for this population.